Rancang Bangun Sistem Analisa Biaya Manfaat Ternak Sapi Berdasarkan Berat Badan Sapi - Emyr Riyanda Azra; Dodon Yendri; Adrizal (Universitas Andalas, 2023)
Cattle fattening proccess is very important to increase the weight of cattle before being sold. However, there are many traditional breeders looking for cows that have reached puberty, but the cow's body is still thin. This could be due to the absence of records in monitoring the weight growth of cows so that feeding becomes less precise. Based on these problems, a system was designed that helps farmers in managing their livestock management by recording the progress of each beef cattle that are kept, regulating cattle feeding so that it is more optimal, and knowing the cost benefits of cattle that are kept based on the growth of cow body weight. This system uses two load cells to weigh cows. The weight of the weighed cow can be stored in the web application database. The main function of this system is to be able to calculate and display the cost of benefits of cattle based on the growth of the cow's body weight. Based on the tests carried out, the system can weight cows using two 500kg load cells with an error value of 3.61%. The system can check cow data using keypad input with an average time of 3.99 seconds and store cattle data in the database with an average time of 4.99 seconds. The system can calculate the cost of cow feed needs in one month and income due to changes in cow weight with a 100% success rate.